Efektivitas Model Pembelajaran Inkuiri Terbimbing dalam Meningkatkan Kemampuan Proses Sains dan Keterampilan Berpikir Kritis Peserta Didik Kelas IV SDN Sanolo - Sukaisih, Elfi; Nurwalidainismawati, Nurwalidainismawati; Ramdani, Nurlailatun (STKIP HARAPAN BIMA, 2026)
Scientific process skills and critical thinking skills are two essential competencies that must be developed from the elementary school level, as they serve as the foundation for facing 21st-century challenges. This study aims to determine the effectiveness of the guided inquiry learning model in improving students’ scientific process skills and critical thinking skills. The research method used in this study is quantitative research with a quasi-experimental approach. The study was conducted at SDN Sanolo with 30 fourth-grade students. The research design used was a one-group pretest-posttest design with one experimental class. Descriptive data analysis of scientific process skills and cognitive aspects of critical thinking skills used the N-Gain test; furthermore, the data were analyzed using a paired sample t-test. The analysis results show that the N-Gain score obtained was 0.71 for scientific process skills and 0.74 for critical thinking skills; these results fall into the high category, indicating that the implementation of the guided inquiry learning model is effective in improving scientific process skills and critical thinking skills. In addition, the paired sample t-test yielded a Sig. (2-tailed) value of 0.000 0.05, meaning that the guided inquiry learning model has a significant effect on students scientific process skills and critical thinking skills. Therefore, it can be concluded that the guided inquiry learning model is effective in enhancing students’ scientific process skills and critical thinking skills